2017
DOI: 10.1534/genetics.116.199331
|View full text |Cite|
|
Sign up to set email alerts
|

Editing of Mitochondrial Transcripts nad3 and cox2 by Dek10 Is Essential for Mitochondrial Function and Maize Plant Development

Abstract: Respiration, the core of mitochondrial metabolism, depends on the function of five respiratory complexes. Many respiratory chain-related proteins are encoded by the mitochondrial genome and their RNAs undergo post-transcriptional modifications by nuclear genome-expressed factors, including pentatricopeptide repeat (PPR) proteins. Maize () is a classic mutant with small kernels and delayed development. Through positional cloning, we found that encodes an E-subgroup PPR protein localized in mitochondria. Sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 56 publications
3
63
0
Order By: Relevance
“…When the main electron transfer chain is impaired, alternative and compensatory respiration pathways can be activated (Kühn et al ., ). Because several mutants with impaired mitochondrial complex I showed the induction of AOX expression (Li et al ., ; Chen et al ., ; Xiu et al ., ; Cai et al ., ; Lee et al ., ; Qi et al ., ,b; Ren et al ., ; Zhang et al ., ; Dai et al ., ), we measured total respiration rate (V t ), the capacities of the alternative respiratory pathway (V alt ), and the capacities of the cytochrome respiratory pathway (V cyt ) using a combination of specific inhibitors (Sun et al ., ). The results showed that V t was markedly reduced in the emp8 mutant (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the main electron transfer chain is impaired, alternative and compensatory respiration pathways can be activated (Kühn et al ., ). Because several mutants with impaired mitochondrial complex I showed the induction of AOX expression (Li et al ., ; Chen et al ., ; Xiu et al ., ; Cai et al ., ; Lee et al ., ; Qi et al ., ,b; Ren et al ., ; Zhang et al ., ; Dai et al ., ), we measured total respiration rate (V t ), the capacities of the alternative respiratory pathway (V alt ), and the capacities of the cytochrome respiratory pathway (V cyt ) using a combination of specific inhibitors (Sun et al ., ). The results showed that V t was markedly reduced in the emp8 mutant (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Although with sequence similarity among the PPR motifs, PPRs exhibit functional distinction and non-redundancy in assisting the organelle expression and evolutional diversity between monocots and eudicots Barkan and Small, 2014;Manna, 2015). The PLS (repeat P-L-S motif)-subfamily PPRs predominantly assist in RNA editing (Takenaka et al, 2013;Barkan and Small, 2014;Li et al, 2014;Sun et al, 2015;Qi et al, 2017b;Wang et al, 2017b;Yang et al, 2017) and RNA splicing (Chateigner-Boutin et al, 2011;Ichinose et al, 2012), whereas the P subfamily PPRs have been functionally characterized in mitochondrial intron splicing (Brown et al, 2014;Hsu et al, 2014;Hsieh et al, 2015;Chen et al, 2016;Xiu et al, 2016;Cai et al, 2017;Qi et al, 2017a;Ren et al, 2017;Dai et al, 2018), transcript stabilization (Colas des Francs- Lee et al, 2017;Wang et al, 2017a;Zhang et al, 2017), cleavage and translation (Colas des Francs- Ha€ ıli et al, 2016). Nonetheless, the number of characterized mitochondrial PPRs involved in the splicing of group II introns is very few, especially for the case of mutations leading to embryo lethality which often negates genetic and molecular studies (Barkan and Small, 2014;.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, C‐to‐U editing at nad genes is critical to the function of complex I. Disrupted functions of complex I were detected because of the lack of RNA editing at nad7‐ 836 ( smk1 ) (Li et al ), nad3‐ 250 ( slg1 ) (Yuan and Liu ), nad3‐ 61, and nad3‐ 62 ( dek10 ) (Qi et al ). However, mutation in Mef9 and Mpr25 failed to edit site nad7‐ 200 and nad5‐ 1580, respectively, which did not affect the NADH dehydrogenase activity of complex I (Takenaka ; Toda et al ; Yap et al ).…”
Section: Discussionmentioning
confidence: 99%
“…CRR22 (Okuda et al 2009) and MEF1 (Zehrmann et al 2009) are involved in at least three sites in plastids and three sites in mitochondria, respectively. PPR2263, EMP9, DEK10 are also trans-factors required in multiple sites editing (Sosso et al 2012;Qi et al 2017a;Yang et al 2017). PPR proteins such as SLG1, SMK1 and EMP7 have been reported to be responsible for single editing sites as well (Yuan and Liu 2012;Li et al 2014;Sun et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations of these genes impair mitochondral function, leading to defective kernels. Other genes, including EMP7 (Sun et al, 2015), DEK10 (Qi et al, 2017), DEK39 (Li et al, 2018), PPR2263/MITOCHONDRIAL EDITING FACTOR29 (Sosso et al, 2012), and SMALL KERNEL1 (Li et al, 2014) function in C-to-U editing of transcripts in mitochondria and chloroplasts.…”
Section: Introductionmentioning
confidence: 99%